2003
DOI: 10.1002/chin.200310138
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N‐Vinyl‐1,2,3‐triazole Derivatives.

Abstract: Triazole derivatives Triazole derivatives R 0280Synthesis of N-Vinyl-1,2,3-triazole Derivatives. -The synthesis of 1-vinyl-1,2,3-triazole and its previously unknown nitro derivatives (III) by vinyl exchange reaction promoted by a catalytic system consisting of Hg(O-Ac) 2 /TFA is described. -(KIZHNYAEV, V. N.; POKATILOV, F. A.; TSYPINA, N. A.; RATOVSKII, G. V.; VERESHCHAGIN, L. I.; SMIRNOV, A. I.; Russ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Current methods for preparing N -vinyl derivatives of secondary amines involve the vinyl exchange reaction ( Scheme 1 , route a), which requires a source of vinyl group (in most cases represented by vinyl acetate) and a metal catalyst. Enamines from nitrogenous bases [ 7 ], imidazole [ 8 ], triazoles [ 9 ], carbazole [ 10 ], and pyrrolidone [ 11 ] can be successfully obtained by this approach.…”
Section: Introductionmentioning
confidence: 99%
“…Current methods for preparing N -vinyl derivatives of secondary amines involve the vinyl exchange reaction ( Scheme 1 , route a), which requires a source of vinyl group (in most cases represented by vinyl acetate) and a metal catalyst. Enamines from nitrogenous bases [ 7 ], imidazole [ 8 ], triazoles [ 9 ], carbazole [ 10 ], and pyrrolidone [ 11 ] can be successfully obtained by this approach.…”
Section: Introductionmentioning
confidence: 99%
“…Since VT is a weak base (p = 3.11), the kinetic parameters of the polymerization reaction will probably depend on the pH of a medium. For example, the authors of [ 42 ] showed that the rate of reaction is described by an extremal curve with a minimum at pH ~7. Reduction in pH from 7 to 3 leads to an increase in the rate of reaction, which is promoted by triazole ring protonation, and, accordingly, enhances electron-acceptor properties of the triazole ring and radical of a growing macromolecule.…”
Section: Synthesis Of Poly(1-vinyl-124-triazole)mentioning
confidence: 99%
“…Relying on the propensity of the triazole cycles to generate diverse weak interactions (such as H-bonding), the same research group further investigated the influence of the polymerization medium on the kinetics of 1-vinyl-1,2,3-triazole 52 polymerization. 22 The influence of water, acetic acid and their mixtures with acetonitrile was carefully examined. It was shown that the addition of protic species has a substantial acceleration effect on the polymerization process as confirmed by the significant rise of k p /k t 0.5 from 0.54 at 60 C in acetonitrile to 2.25 and 1.94 (l/(mol s)) 0.5 respectively in water and acetic acid.…”
Section: -Vinyl-123-triazole-based Glycopolymers Obtained By Raft Pol...mentioning
confidence: 99%